DEVELOPING MIND MAPPING TECHNIQUE IN TEACHING WRITING DESCRIPTIVE TEXT GRADE XI AT SMAN 1 SIBORONGBORONG - Elsa Ompusunggu; Elia Masa Gintings; Yeni Elita (Universitas Negeri Medan, 2019)
This research was aimed at develops technique as media in teaching writing descriptive texts. This study was conducted using R & D method by Borg & Gall (2003). The research took place at SMAN 1 Siborongborong. The sample consisted of class 11-XI. The evaluators of the media were two experts. The instruments employed in this study were questionnaire, interview, and test. The findings of the study were the quality of the developed technique as media viewed from the experts is very good (88 %). The final product of the technique as media was assessed by gave questionnaires to the students to know the students’ responses about the media. Most students gave positive responses. Most students said that the media was interesting and it could help them to understand descriptive texts easily. The results of the test show that the technique as media improved their ability in writing descriptive texts (average score: 80, 12).The scoring system was based on five aspects; namely content, organization, vocabulary, language use, mechanics. Therefore, the writer suggests that English teachers develop technique as one of the creative way to improve the students’ ability in writing descriptive texts.Keywords: Descriptive texts, pictures, writing.